The Buryat influence on the Barguzin Evenki people and their language - Khabtagaeva (2014)
The paper presents a short overview of the Barguzin Evenki people and on some linguistic criteria which help to distinguish late Mongolic (or Buryat) borrowings from the early loanwords. The Barguzin Evenki people, a small Tungusic group, live in the territory of Buryatia, Russia. In spite of the fact that they have lived among Buryats for quite a long period, they have preserved their language and culture. All of them are trilingual: they speak Evenki, Buryat and Russian.